2017
DOI: 10.1007/s00404-017-4554-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pelvic artery embolisation for severe postpartum hemorrhage

Abstract: This is the first controlled study assessing the efficacy of PAE for the treatment of PPH. Our data suggest that PAE is effective for the treatment of severe PPH. In view of the lack of complications and unwarranted effects, clinical use of PAE in severe PPH seems justified, particularly in view of the life-threatening condition and the potential to preserve fertility in affected patients. Further evidence from well-designed prospective randomized-controlled trials would be nevertheless desirable in the future. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…12 The success rate of transcatheter arterial embolization varies between 85% -100%. 1,6,7,10,13 Complication rates related with arterial embolization are low, ranging between 6% -9%, including post-embolization syndrome (transient fever, pelvic pain and nausea), intra-abdominal hematoma, uterine necrosis, artery dissection, lower limb ischemia, endometritis, amenorrhea and sepsis. 11,[13][14][15] We consider this case a success, as selective arterial embolization allowed hemorrhage control in an unstable patient with disseminated intravascular coagulopathy, thus minimizing the bleeding risks associated with major anesthetics and surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The success rate of transcatheter arterial embolization varies between 85% -100%. 1,6,7,10,13 Complication rates related with arterial embolization are low, ranging between 6% -9%, including post-embolization syndrome (transient fever, pelvic pain and nausea), intra-abdominal hematoma, uterine necrosis, artery dissection, lower limb ischemia, endometritis, amenorrhea and sepsis. 11,[13][14][15] We consider this case a success, as selective arterial embolization allowed hemorrhage control in an unstable patient with disseminated intravascular coagulopathy, thus minimizing the bleeding risks associated with major anesthetics and surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…4 Post-partum hemorrhage that occurs in the first 24 hours after delivery is considered primary and is mostly due to uterine atony, genital tract lacerations, placental retention, abnormal placentation or coagulopathy. 2,[5][6][7] We present a rare case of right uterine and cervical laceration after vacuum-assisted delivery resulting in disseminated intravascular coagulopathy, treated with uterine artery embolization and hysterectomy…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned treatments are considered the optimal modalities to manage a patient with an atonic uterus and hemorrhage, who is at risk of hypovolemic shock and collapse (35). In cases of failure of these approaches, uterine artery ablation and caesarean hysterectomy are the final resorts used to prevent maternal death as a result of the severe hemorrhage (36).…”
Section: Non-obstetric Indicationsmentioning
confidence: 99%
“…Some studies [ 4 , 8 , 9 , 11 16 ] have suggested that estimated blood loss, hemoglobin concentrations, and total blood transfusion volume might be associated with the failure of UAE. The amount of blood loss during the perinatal period may be underestimated [ 19 ]. Additionally, the volumes of blood loss and blood transfused are based on the final state of the patient, and are not useful for predicting the failure of UAE.…”
Section: Case Presentationmentioning
confidence: 99%